Edukasi Tentang Tablet Tambah Darah Sebagai Upaya Pencegahan Anemia Pada Remaja Putri Di Kabupaten Bantul - Retno Heru Setyorini; Era Revika; Fitriani Mediastuti (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2025)
Anemia is one of the nutritional problems of adolescents in Indonesia. One of the efforts to prevent anemia in adolescent girls is by providing iron tablets. However, many adolescent girls are still not obedient in taking iron tablets. Lack of knowledge is one of the factors causing the behavior of adolescent girls in taking iron tablets. The purpose of this activity is to provide education about iron tablets to adolescent girls in high schools in Bantul Regency to improve the behavior of taking iron tablets by increasing knowledge, attitudes, intentions and subjective norms. Lectures and questions and answers using LCD and Power Point media are used to implement the activity. Materials on anemia, iron tablets, personal hygiene during menstruation, and stunting were given by two lecturers from the Akbidyo Health Sciences College. The knowledge, attitudes, and intentions of adolescent girls about iron tablets increased. It is necessary to strengthen the role of teachers, friends, and parents to provide information about iron tablets as an effort to prevent anemia in adolescent girls.